2020
DOI: 10.1016/j.cell.2020.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Type V Collagen in Scar Tissue Regulates the Size of Scar after Heart Injury

Abstract: Highlights d Collagen V deficiency increases scar size after acute heart injury d Mechanical properties of scars are altered with Col V deficiency d Altered mechanosensitive cues augment myofibroblast formation in scar d Inhibition of specific integrins rescues increased scarring in Col-V-deficient states

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
98
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(111 citation statements)
references
References 66 publications
3
98
0
Order By: Relevance
“…Studies have also shown that both collagen receptor integrin and hyaluronan acid receptor CD44 are involved in the mechanical conduction of ECM stiffness ( 13 ). Specifically, hyaluronan acid with different molecular weights binds to its receptor CD44, whereas collagen components of various subtypes bind to corresponding integrin receptor subtypes, regulating downstream signal pathways and producing different biological effects ( Table 1 ).…”
Section: Extracellular Matrix Components and Mechanical Biological Comentioning
confidence: 99%
“…Studies have also shown that both collagen receptor integrin and hyaluronan acid receptor CD44 are involved in the mechanical conduction of ECM stiffness ( 13 ). Specifically, hyaluronan acid with different molecular weights binds to its receptor CD44, whereas collagen components of various subtypes bind to corresponding integrin receptor subtypes, regulating downstream signal pathways and producing different biological effects ( Table 1 ).…”
Section: Extracellular Matrix Components and Mechanical Biological Comentioning
confidence: 99%
“…Besides, the histopathological features of skin and lung in a animal model of systemic sclerosis induced by type V collagen revealed that increased collagen V fibers and COL5A1 gene expression ( Teodoro et al, 2019 ). The study by Yokota et al (2020) demonstrated that type V collagen played a crucial role in scar size following myocardial infarction and induced fibroblast activation. Therefore, based on the regulatory role of COL5A1 in these fibrosis diseases, it could be speculated that COL5A1 might be associated with the pathogenesis of keloids and have the potential to serve as a novel therapeutic target.…”
Section: Introductionmentioning
confidence: 99%
“…Based on in situ hybridization analysis, Roulet's group reported that the expression of COL5A1 plays an important role in the development of functional connective tissues, especially in the heart, dorsal aorta wall, skin, and vertebral column, suggesting that COL5A1 plays an important role in the development of these organs in developing embryos (Roulet et al, 2007). Interestingly, Yokota et al (2020) found that the COL5A1 expression level significantly correlated with scar size after myocardial infarction mechanically, not only in the regulation of the size of cardiac scars but also in tissue mechanical properties in an integrin-dependent manner. The expression level of B2M in the plasma is not simply a significant marker for kidney injury but a novel regulator involved in heart failure and heart remodeling (Vianello et al, 2015).…”
Section: Discussionmentioning
confidence: 99%